Reorienting Islamic curriculum and pedagogy in Indonesia: Aligning with national character education policy - Alhamuddin Alhamuddin; Abdul Gafur Arifin (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2025)
Although character values are embedded in the Islamic education curriculum in Indonesia, a gap persists between policy and classroom implementation. The main objective of this study is to reorient Islamic curriculum and pedagogy in alignment with Indonesia’s national character education policy. This study explores how character education is applied in Islamic education through curriculum, teaching, and assessment. A mixed-methods approach was used, combining a survey of 22 teachers and analysis of curriculum documents. The findings revealed that while values such as honesty, responsibility, and respect were included in lesson plans and textbooks, they were rarely implemented through interactive teaching methods or assessed using formal tools. Most teachers used lectures and moral preaching, with limited application of reflective or student-centered strategies. The study concludes that character education remains superficial without integrated pedagogy and assessment. The proposed reoriented model suggests a threefold transformation. First, policy-aligned value mapping should explicitly link Islamic moral concepts with the six dimensions of the Pancasila Student Profile. Second, reflective pedagogies must replace or complement the current didactic model. Third, assessment reform is essential. These findings offer insights for policymakers and educators seeking to enhance the effectiveness of character education in schools.